Binding mechanism and antioxidant capacity of selected phenolic acid - β-casein complexes. (March 2020) - Li, Ti; Li, Xin; Dai, Taotao; Hu, Peng; Niu, Xiaoqin; Liu, Chengmei; Chen, Jun
Graphical abstract: Highlights: The structural characteristic of phenolic acids affected affinities ability with β-CN. The main driving force with β-CN was influenced by type of phenolic acids. Binding of phenolic acids lead to loss of random coil structure of β-CN. Binding to β-CN weaken the activity of phenolic acids. Abstract: Phenolic acids are added to some dairy products as functional ingredients. The molecular interactions between the phenolic acids and milk proteins impacts their functional performance and product quality. In this study, the interactions between a milk protein (β-casein) and a number of phenolic acids was investigated: 3, 4-dihydroxybenzoic acid (DA); gallic acid (GA); syringic acid (SA); caffeic acid (CaA); ferulic acid (FA); and, chlorogenic acid (ChA). The structural characteristics of the phenolic acids, such as type, hydroxylation, methylation, and steric hindrance, affected their binding affinity to β-casein. The strength of the binding constant decreased in the following order: CaA > ChA > FA > SA > GA > DA. Cinnamic acid derivatives (CaA, FA, and ChA) exhibited a stronger binding affinity with β-casein than benzoic acid derivatives (DA, GA, and SA). Hydrophobic forces and electrostatic interactions dominated the interactions of β-casein with benzoic acid and cinnamic acid derivatives, respectively. The number of hydroxyl groups on the phenolic acids enhanced their binding ability, while steric hindrance effects reduced their binding ability. The influence of methylation depended on phenolic acid type. After binding with phenolic acids, the conformation of the β-casein changed, with a loss of random coil structure, an increase in α-helix structure, and a decrease in surface hydrophobicity. Furthermore, the presence of β-casein decreased the in vitro antioxidant capacities of the phenolic acids, especially for gallic acid. These findings provide some useful insights into the structure–activity relationships of the interaction between β-casein and phenolic acids.